PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Rahma Puspa Wigati; Listyorini Wahyu Widati (Jurnal Riset Akuntansi Politala, 2023)
The population in this study are all Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange 191 companies in the 2019-2021 period. The sampling technique used was purposive sampling, so the final sample obtained was 186 companies belonging to the Consumer Goods Industry sector on the Indonesia Stock Exchange for the 2019-2020 period. In this study the method of data analysis using multiple linear regression analysis. The results of this study explain that company size and inventory turnover have a positive effect on profitability, while leverage has a negative effect on profitability.